Analysis of Financial Performance Efficiency at the National Amil Zakat Agency (BAZNAS) East Java Province 2018-2020 Period Using Data Envelopment Analysis and the National Zakat Index - Sri Wahyuni ​​ Ningsih; Indah Yuliana (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
Zakat plays an important role in improving the welfare of a country, especially in supporting economic growth, in this case the government establishes BAZNAS in charge of Managing, Distributing and Empowering Zakat. To know the performance of BAZNAS, it is necessary to evaluate the efficiency. The purpose of this study was to determine the efficiency of the performance of BAZNAS JATIM for the 2018-2020 period by using two approach methods, namely Data Envelopment Analysis and the National Zakat Index. The results of the study using DEA show that the performance of BAZNAS is efficient with an efficiency line of 100% from 2018-2020 and the results using the IZN method show that there was an increase in regulation, which initially in 2018 the regulatory indicator o btained an index value of 0, which means it is not good, has increased in 2019-2020 it was also known that the regulatory indicator scored 1.00 (very good) which means the local government has issued regulations related to zakat. Regarding the allocation of APBN/APBD funds, there is also an increase, namely the indicator value of APBN support is 0.25 (not good), which means that at least 20% of the operational costs of the East Java Baznas can be met with the budget. Keywords: performance efficiency, BAZSNASJATIM, Data Envelopment Analysis, National Zakat Index,